Leadership in doctor-patient relationship: Implementation on patient's case management in primary care (Faculty of Medicine Universitas Indonesia, 2017)
As a care coordinator, primary care physicians (PCP) need planning, organizing, implementation, and evaluation. A model of leadership in medicine needs to be implemented in primary care. Transformational leadership is defined as a leadership style that is suitable for health services. It is similar to a patient-centered approach. Case management should be well prepared and explained in accordance with patient needs, can be agreed upon, as well as implemented with appropriate respective roles. A leader needs to do various aspects related to the managerial process for carrying out the required activities. The same process can also be done by PCPs to achieve patient's target management. Such activities include planning up to building networks. PCPs are expected to have leadership competencies and transformational leadership to support their performance as care coordinators. This can be obtained through a holistic, comprehensive, integrated, and continuous approach, as well as building relationships with other stakeholders.